Autoimmune diseases and new-onset atrial fibrillation: a UK Biobank study - Tilly, Martijn J; Geurts, Sven; Zhu, Fang; Bos, Maxime M; Ikram, M Arfan; de Maat, Moniek P M; de Groot, Natasja M S; Kavousi, Maryam (Europace (London, England), 2023)
Abstract Aims The underlying mechanisms of atrial fibrillation (AF) are largely unknown. Inflammation may underlie atrial remodelling. Autoimmune diseases, related to increased systemic inflammation, may therefore be associated with new-onset AF. Methods and results Participants from the population-based UK Biobank were screened for rheumatic fever, gastrointestinal autoimmune diseases, autoimmune diseases targeting the musculoskeletal system and connective tissues, and neurological autoimmune diseases. Between 2006 and 2022, participants were followed for incident AF. Cox proportional hazards regression analyses were performed to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) to quantify associations. 494 072 participants free from AF were included (median age 58.0 years, 54.8% women). After a median of 12.8 years, 27 194 (5.5%) participants were diagnosed with new-onset AF. Rheumatic fever without heart involvement (HR, 95% CI: 1.47, 1.26–1.72), Crohn’s disease (1.23, 1.05–1.45), ulcerative colitis (1.17, 1.06–1.31), rheumatoid arthritis (1.39, 1.28–1.51), polyarteritis nodosa (1.82, 1.04–3.09), systemic lupus erythematosus (1.82, 1.41–2.35), and systemic sclerosis (2.32, 1.57–3.44) were associated with a larger AF risk. In sex-stratified analyses, rheumatic fever without heart involvement, multiple sclerosis, Crohn’s disease, seropositive rheumatoid arthritis, psoriatic and enteropathic arthropathies, systemic sclerosis and ankylosing spondylitis were associated with larger AF risk in women, whereas only men showed a larger AF risk associated with ulcerative colitis. Conclusions Various autoimmune diseases are associated with new-onset AF, more distinct in women. Our findings elaborate on the pathophysiological differences in autoimmunity and AF risk between men and women. Graphical Abstract Graphical Abstract